Session Topic: Allocational Efficiency of Security Markets Under Uncertainty: Discussion - Kraus, Alan; Grauer, Frederick L. A. (Journal of Finance, 1976)
Alan Kraus, Frederick L. A. Grauer, Session Topic: Allocational Efficiency of Security Markets Under Uncertainty: Discussion, The Journal of Finance, Vol. 31, No. 2, Papers and Proceedings of the Thirty-Fourth Annual Meeting of the American Finance Association Dallas, Texas December 28-30, 1975 (May, 1976), pp. 602-609